TRAINING PhDs IN EDUCATION ON RESEARCH METHODOLOGY - Sysoіeva, Svitlana (The Modern Higher Education Review, 2017)
On the basis of studying the US experience on the content of training PhDs in education the author presents the program on research methodology in education for training PhDs in education. The purpose of the course is to develop future scientists methodological culture, integrated system of scientific knowledge, the ability to organize and conduct research in the field of education, including disciplinary and interdisciplinary research, and it is aimed at forming  a system of research competencies.